2021
DOI: 10.1002/cne.25278
|View full text |Cite
|
Sign up to set email alerts
|

The pigment‐dispersing factor neuronal network systematically grows in developing honey bees

Abstract: The neuropeptide pigment‐dispersing factor (PDF) plays a prominent role in the circadian clock of many insects including honey bees. In the honey bee brain, PDF is expressed in about 15 clock neurons per hemisphere that lie between the central brain and the optic lobes. As in other insects, the bee PDF neurons form wide arborizations in the brain, but certain differences are evident. For example, they arborize only sparsely in the accessory medulla (AME), which serves as important communication center of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 106 publications
(195 reference statements)
0
5
0
Order By: Relevance
“…The expression pattern of PDF in aphid circadian clock neurons strongly resembles that of other insects, [64][65][66][67]. As true for flies, cockroaches, bugs and bees [12,65,[68][69][70], PDF is present in aphid lateral clock neurons with different soma sizes. These clock neurons send projections to the superior protocerebrum and to the contralateral brain hemisphere, more precisely to a neuropil that strongly resembles the accessory medulla (AME) of other insects.…”
Section: The Pdf-positive Clock Neurons In the Aphid Brain Closely Re...mentioning
confidence: 79%
See 1 more Smart Citation
“…The expression pattern of PDF in aphid circadian clock neurons strongly resembles that of other insects, [64][65][66][67]. As true for flies, cockroaches, bugs and bees [12,65,[68][69][70], PDF is present in aphid lateral clock neurons with different soma sizes. These clock neurons send projections to the superior protocerebrum and to the contralateral brain hemisphere, more precisely to a neuropil that strongly resembles the accessory medulla (AME) of other insects.…”
Section: The Pdf-positive Clock Neurons In the Aphid Brain Closely Re...mentioning
confidence: 79%
“…Most interestingly, a rather sparse innervation of the optic lobes by PDF fibres was also found in honeybees [50,70]. Furthermore, many varicose endings and no fine dendritic-like fibres were found in the AME of honeybee larvae.…”
Section: The Pdf-positive Clock Neurons In the Aphid Brain Closely Re...mentioning
confidence: 84%
“…At the brain level, in the fruit fly, it is known that multiple oscillators that control the timing of locomotor activity at different times of the day ( e.g ., morning and evening cells) not only need to communicate but they need to synchronize in a specific manner ( Stoleru et al, 2004 , 2005 ). Recent work in the honey bee tracking the number of Pigment Dispersing Factor (PDF) positive neurons across different ages in the worker has shown that the number of PDF+ neurons and their arborizations to different parts of the bee brain continues to change after emergence ( Beer & Helfrich-Förster, 2020 ; Beer, Härtel & Helfrich-Förster, 2022 ). It is thus possible that the establishment of connections among the multiple components of the circadian system in the honey bee brain occurs in the first 48 h after emergence.…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of PDF in aphid circadian clock neurons strongly resembles that of other insects [ 72 75 ]. As true for flies, cockroaches, bugs and bees [ 18 , 73 , 76 78 ], PDF is present in aphid lateral clock neurons with different soma sizes. These clock neurons send projections to the superior protocerebrum and to the contralateral brain hemisphere, more precisely to a neuropil that strongly resembles the AME of other insects.…”
Section: Discussionmentioning
confidence: 99%
“…This speaks against a prominent role of the AME, or at least the PDF fibres in the AME, as a light-input pathway to the circadian clock neurons. Most interestingly, a rather sparse innervation of the optic lobes by PDF fibres was also found in honeybees [ 51 , 78 ]. Furthermore, many varicose endings and no fine dendritic-like fibres were found in the AME of honeybee larvae.…”
Section: Discussionmentioning
confidence: 99%